2018
DOI: 10.25122/jml-2018-0005
|View full text |Cite
|
Sign up to set email alerts
|

Green tea improves rat sperm quality and reduced cadmium chloride damage effect in spermatogenesis cycle

Abstract: Introduction Testicular tissue is part of the reproductive system that some mineral compounds such as cadmium chloride (CdCl2) destroy. Green tea (Camellia sinensis) extract can reduce the tissue damage caused by toxins due to its antioxidant properties. The aim of this study was to evaluate the effect of green tea extract on sperm quality in cadmium chloride toxicity. Materials and Methods In the present study, male Wistar rats were allotted randomly into four groups, namely control group (C), CdCl2 (1.5mg/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 25 publications
2
15
0
Order By: Relevance
“…Thereby, administration of antioxidants increased semen parameters, including the percentage of motile spermatozoa (Ahmadi et al, 2016). Antioxidants in green tea could prevent oxidative damage due to free radicals on several spermatozoa parameters, such as motility, abnormalities, and concentration (Mahmoudi et al, 2018). However, administration higher dose (60 mg/kg BW) of GTE showed a decrease in the percentage of spermatozoa plasma membrane integrity, viability, and motility.…”
Section: Discussionmentioning
confidence: 96%
“…Thereby, administration of antioxidants increased semen parameters, including the percentage of motile spermatozoa (Ahmadi et al, 2016). Antioxidants in green tea could prevent oxidative damage due to free radicals on several spermatozoa parameters, such as motility, abnormalities, and concentration (Mahmoudi et al, 2018). However, administration higher dose (60 mg/kg BW) of GTE showed a decrease in the percentage of spermatozoa plasma membrane integrity, viability, and motility.…”
Section: Discussionmentioning
confidence: 96%
“…Cadmium is found in batteries, pigments, metal coatings, plastics, and in cigarette smoke. The studies about cadmium exposure on Rats reported that sperm count, motility and vitality as well as morphologically normal sperm and testosterone was significantly reduced (Adamkovicova et al, 2016; Asadi et al, 2013; Mahmoudi et al, 2018). A study conducted on mice suggested that Cd‐induced phosphorylation of proteins might act as an engine to inhibit energy metabolism and decrease sperm motility (Wang et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The standard dose is calculated as the average dosing of body weight-based and body surface area-based dosing (Mokhimar et al, 2020). Two sacrifice days have been placed, the first was on day 15 to evaluate the acute effects, and the second was on day 60 from the first day of treatment, to follow the sperm cycle from the start of spermatogenesis to sperm maturation (Mahmoudi et al, 2018). We observed a significant decrease in sexual organ weight (testis, epididymis) and sperm parameters (count, motility, viability) after treatment with Ciprofloxacin.…”
Section: Discussionmentioning
confidence: 99%